West Africa Regional Training On the Improved NextGen Seasonal Forecasting Approach (PyCPT 2) - Grossi, Amanda; Robertson, Andrew; Trzaska, Sylwia; Dinku, Tufa; Zougmoré, Robert B.; Minoungou, Bernard; Mohamed, Hamatan (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
From October 10-19, a nine-day training targeting West Africa (WA) was implemented in Lomé, Togo by the International Research Institute for Climate and Society (IRI) of the Columbia Climate School, in close collaboration with the AICCRA-West Africa team, the Regional Center for Training and Application in Agrometeorology and Operational Hydrology (AGRHYMET) and Meteo Togo. The workshop, which was organized as part of the World Bank’s Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project, brought together 7 national meteorological services from the WA region, as well as its regional climate center (AGRHYMET) to improve seasonal forecasting capacities using the “NextGen” approach and its concomitant PyCPT version 2 interface (PyCPT2). In particular, the major objectives of the training were to strengthen the knowledge and understanding of national meteorological services of seasonal forecasting tools, introduce the new advances and functionalities of the Python (PyCPT2) interface for the NextGen forecasting approach, configure and run PyCPT version 2 to make the best- available forecasts in participants’ home countries, including forecast verification, and provide foundational training on best practices for forecast communication including the flexible forecast format.